Highly Efficient and Water‐Stable Lead Halide Perovskite Quantum Dots Using Superhydrophobic Aerogel Inorganic Matrix for White Light‐Emitting Diodes. Issue 2 (13th January 2020) - Li, Zongtao; Song, Cunjiang; Li, Jiasheng; Liang, Guanwei; Rao, Longshi; Yu, Shudong; Ding, Xinrui; Tang, Yong; Yu, Binhai; Ou, Jianzhen; Lemmer, Uli; Gomard, Guillaume
Abstract: At present, most of lead halide perovskite quantum dots (PQDs) embedded in an enclosed organic polymer or glass matrix can achieve high water stability, yet this limits their subsequent integration with light‐emitting diodes (LEDs) and other functional materials. Herein, a postadsorption process using superhydrophobic aerogel inorganic matrix (S‐AIM) with open structures is presented to enhance water stability of PQDs and compose new functions to them such as magnetism. The CsPbBr3 PQDs integrated with the S‐AIM (AeroPQDs) exhibit a high relative photoluminescence quantum yield (PLQY, 75.6%) of 90.9% compared to pristine PQDs (PLQY, 83.2%). They preserve their initial PL intensity after 11 days of soaking in water and achieve a high relative PLQY stability (50.5%) after soaking for 3.5 months. The hydrophobic (rough) surface of the matrix, its pores with a well‐matched mean diameter that promotes the homogeneous integration of PQDs and hinders the penetration of water as well as the oleophylic functional groups covering the surface of these pores are the three factors responsible for the high water stability. Finally, AeroPQDs are easily integrated with other functional nanomaterials, such as Fe3 O4 nanoparticles for magnetic manipulation, due to their open structure. Abstract : Lead halide perovskite quantum dots (PQDs) are integrated within superhydrophobic aerogel inorganic matrix via a facile and cost‐effective postadsorption process, effectively enhancing their photoluminescence performance and stability (against water/moisture and UV irradiance). These solid‐state phosphors have great potential in highly efficient and stable white light‐emitting diodes, as well as the fundamental fluorescence integration platform for compounding functional materials, expanding the application scope of PQDs.